Use of dexmedetomidine in total intravenous anesthesia (TIVA) (2011)
Dexmedetomidine was used initially for sedation in intensive care units. However, because of its sedative, analgesic and anti-anxiety effects and the fact that it does not alter ventilatory function, its use may be expanded as an intravenous agent in surgery. There are reports in the literature about its effective use in specific surgical populations, although further studies are required in order to support its use in all situations where total intravenous anesthesia (TIVA) is applied. The purpose of this review is to describe the role of dexmedetomidine in this form of anesthesia. Materials y methods. A literature search was conducted in PubMed, Medline, EMBASE, Cochrane and LILACS. The search was expanded based on the references found in the articles reviewed initially and analyzed by the authors; the search was conducted under the MeSH included as key words below.